Zhaoguang Hu, Xinyanh Han, & Quan Wern, Integrated Resource Strategic Planning and Power Demand-Side Management - HU, Zhaoguang (Journal of Economics Library, 2015)
Abstract. The edited volume presents an engaging cartography of Indian economy following two decades of liberalization on the backdrop of globalization and problem of sustainability - two defining moments of post-reforms reorganization of the economy. A wide variety of sector-specific and economy-wide studies in the collection, examine the central tenets of market-centric reforms representing globalization. The research works dealing with micro- and macro-aspects of development help us form an idea of important issues, emerging debates, dominant institutions and changes required for attainment/restoration of efficiency. Most of these writings indicate the limitations of current developmental logic in their specific settings. These studies also propose measures to tackle the problems faced while presuming growth-sustainability disconnect to be temporary in nature. A number of studies introduced new analytical categories and empirical frameworks to capture current reality in better and more meaningful ways. A third strand of writings portrays conflict between the project of globalization and issue of sustainability as a distinguishing characteristic of global capitalism although the present policy framework accord highest priority to capitalist expansion. This conflict however, has put the Indian state in a perpetual act of balancing the growth objective of global capital and welfare objective meant for those experiencing exclusion in the development process.. Keywords. Low-carbon electricity, Demand side management, Integrated resource strategic planning, Efficiency power plant, Renewable energy, Ddemand response, Sustainable development, CO2 emissions in China. JEL. P28, Q01, Q20, Q28, Q30, Q40, Q50.